Successful resuscitation after hyperkalemic cardiac arrest during liver transplantation by converting veno-venous bypass to veno-arterial ECMO. (October 2021) - Van Hoof, Lucas; Rega, Filip; Devroe, Sarah; Degezelle, Karlien; Pirenne, Jacques; Neyrinck, Arne
Introduction: Intraoperative cardiac arrest (ICA) is a feared complication during liver transplantation (LTx), typically occurring during reperfusion. Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) has been used for post-reperfusion cardiac arrest. Case report: We present a case of successful resuscitation after hyperkalemic ICA during the pre-anhepatic phase of a second liver transplantation by converting veno-venous bypass (VVB) to VA-ECMO. Discussion: While this technique has been recommended for ICA during reperfusion, it has never been reported during the pre-anhepatic phase. VA-ECMO can be a lifesaving extension to cardiopulmonary resuscitation for ICA during LTx with beneficial neurological outcome by providing perfusion while the cause of ICA is reversed. Conclusion: Conversion of VVB to VA-ECMO should be considered in all patients who suffer from ICA during LTx with use of VVB. With VVB installed, conversion to VA-ECMO is fast and effective. If VVB is not used, early VA-ECMO should be considered for ICA.